2021
DOI: 10.1128/jvi.01998-20
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Ribosome Entry Site of Dengue Virus mRNA Is Active When Cap-Dependent Translation Initiation Is Inhibited

Abstract: Dengue virus (DENV) is an enveloped, positive-sense, single-stranded RNA virus belonging to the Flaviviridae family. Translation initiation of the DENV mRNA can occur following a cap-dependent or a cap-independent mechanism. Two non-mutually exclusive cap-independent mechanisms of translation initiation have been described for the DENV mRNA. The first corresponds to a 5′end-dependent internal ribosome entry site (IRES)-independent mechanism, while the second relies on IRES-dependent initiation. In this report,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 58 publications
5
31
0
Order By: Relevance
“…Using DENV and ZIKV, this mechanism was later shown to be mediated by an internal ribosomal entry site (IRES localized in viral -UTR [4]. A recent report has confirmed the existence of the IRES element [5], indicating, along with previous suggestions [3,6,7] that a cap-dependent translation would be used for viral polyprotein synthesis until the suppression of canonical translation initiation when a switch to cap-independent translation would take place. This alternative cap-independent mechanism, including cell conditions to promote the switch in translation mode, remains to be fully characterized.…”
Section: Introductionmentioning
confidence: 83%
“…Using DENV and ZIKV, this mechanism was later shown to be mediated by an internal ribosomal entry site (IRES localized in viral -UTR [4]. A recent report has confirmed the existence of the IRES element [5], indicating, along with previous suggestions [3,6,7] that a cap-dependent translation would be used for viral polyprotein synthesis until the suppression of canonical translation initiation when a switch to cap-independent translation would take place. This alternative cap-independent mechanism, including cell conditions to promote the switch in translation mode, remains to be fully characterized.…”
Section: Introductionmentioning
confidence: 83%
“…The non-canonical mechanism of translation initiation is undoubtedly characteristic of mRNAs of the Flaviviridae family members: Zika virus (ZIKV), West Nile virus (WNV), yellow fever virus (YFV), and the aforementioned DENV. Although these mRNAs are capped, their efficient translation continues after inactivation of eIF4E and eIF4G, and the presence of a functional cap is not necessary [ 25 , 174 , 175 ]. According to some data, this property is completely determined by the 5′ UTR of viral mRNA [ 174 , 175 ], while according to others, it also requires interaction of 5′ and 3′ UTR [ 25 ], yet the above-described cHP hairpin in the coding part is not required for this.…”
Section: Internal Translation Initiationmentioning
confidence: 99%
“…Although these mRNAs are capped, their efficient translation continues after inactivation of eIF4E and eIF4G, and the presence of a functional cap is not necessary [ 25 , 174 , 175 ]. According to some data, this property is completely determined by the 5′ UTR of viral mRNA [ 174 , 175 ], while according to others, it also requires interaction of 5′ and 3′ UTR [ 25 ], yet the above-described cHP hairpin in the coding part is not required for this. Although in 2006 it was demonstrated [ 25 ] that the 5′ UTR of the DENV mRNA had no IRES activity, two recent studies [ 174 , 175 ] dispute this statement.…”
Section: Internal Translation Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it has been recently found that cap-dependent translation initiation and cap-independent translation initiation mechanisms alternate in DENV infected cells. Interestingly, the weak activity of DENV IRES-like was enhanced in cells expressing the rhinovirus 2A protease, suggesting that the DENV IRES activity enables viral protein synthesis under conditions that suppress cap-dependent translation initiation [ 38 ].…”
Section: Viral Rna Translation: Strategies To Overcome the Inhibition Of Protein Synthesis In Infected Cellsmentioning
confidence: 99%